DEVELOPMENT OF KNOWLEDGE MANAGEMENT SYSTEM FOR JAIPONG DANCE - Feta, Neneng Rachmalia (LPPM Universitas Nusa Mandiri, 2022)
Knowledge for culture is a concept of using information and communication technology to increase usability in the field of culture, especially in managing, documenting, disseminating information and knowledge of cultural arts, especially Sundanese cultural arts, namely the art of jaipong dance. For the art of jaipong dance to be maintained, it is necessary to manage information and knowledge that utilizes the sophistication of information and communication technology towards the noble values ​​of jaipong dance. In that way, the art of jaipong dance can be passed on to each generation to maintain culture as self-identity and show the existence of Sundanese culture in the eyes of the national and even the world. Knowledge Management Systems (KMS) is a solution that can be used to preserve the art of jaipong dance in Indonesia by managing existing knowledge about various things about the art of jaipong dance. The research method uses an integrated knowledge system management cycle. There are three main stages: knowledge capture and/or creation, knowledge sharing and dissemination, and knowledge acquisition and application. Meanwhile, for the formation of knowledge used in this study, the SECI Nonaka model was used. KMS itself can benefit experts, organizations, and the general public. It becomes learning material for every generation. The process of transferring information and knowledge about the movements in the Jaipong dance what musical instruments are used in performances, fashion, and make-up can run. properly and can preserve the art of jaipong dance, which is one of the characteristics of dance in Indonesia.